THE SHIFT OF ACEHNESE LANGUAGE IN PULAU KAMPAI COMMUNITY, NORTH SUMATRA - Chairuddin Chairuddin (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2018)
This Study deals with “The Shift of Acehnese Language in Pulau Kampai Community”.The aims of this research are: (1) to obtain the reasons of language shifting that has happened in Pulau Kampai?  (2).to find out what factors that caused shifting of Acehnese language in Pulau Kampai.This research use the qualitative descriptive, The Subject of research is the second generation of Acehnese community in Pulau Kampai. The Researcher found that the shifting pattern of Acehnese language among Acehnese community in Pulau Kampai is bilingual subordinate patterns that exist in the second stage. The Acehnese community (in this case, second generation) still uses Acehnese language predominantly but there are some new words that come from other languages that are used to replace some words in Acehnese.The shifting of Acehnese language happened caused by four factor that interconnected between one and the other. The four factors include (1). Migration (Acehnese community in Pulsu Kampai is a newcomers from the other areas, that are Beurenuen, Sigli, Tamiang and Aceh Timur, (2). Number of the speaker (Acehnese community is minority community, (3) Demographic, (Location of new area), and (4) Economic (a condition that requires Acehnese people to meet or join with other workers)caused a shifting of language.